Design and analysis of CPW based shunt capacitive RF MEMS switch. Issue 1 (1st January 2017) - Lakshmi Narayana, T.; Girija Sravani, K.; Srinivasa Rao, K.
Abstract: This paper is about, the design and analysis of shunt capacitive RF MEMS switch with less actuation voltage, low insertion losses and high isolation losses. The switch design is incorporated the Electrostatics MEMS actuation technique with vertically deforming bridge. In terms of actuation voltage the switch performance is improved by choosing step type actuation structure with holes. The switch Radio Frequency (RF) performance is analysed over the frequency range from 0.6 to 40 GHz. The major achievements in this work are actuation voltage is reduced to 4.2 V for 0.9 μm displacement, the return loss is below −16 dB, the insertion loss is below −0.44 dB, and the isolation loss is −20 dB. The dielectric material used between the membrane and the CPW line is Aluminum Nitride (AlN) with dielectric constant 9.5. The substrate material used for the CPW transmission line is quartz with dielectric constant 3.9. The bridge is designed with meanders, step structure by using gold material with thickness 0.5 μm. The switch upstate capacitance is capacitance ratio of the shunt capacitive switch is 65.22.